Penerapan Mikrotik Dalam Mengembangkan Infrastruktur Jaringan Pada Kantor Desa Rumbuk Kecamatan Sakra - YUPI KUSPANDI PUTRA; Muhamad Sadali; Mahpuz Mahpuz (Fakultas Teknik Universitas Hamzanwadi, 2020)
The network topology used in the Rumbuk village office is a star topology, where every PC / computer in each room is connected using a UTP cable. While all mobile phones are connected wirelessly (without cable) through the access point on the modem. The problem with this network infrastructure is in managing hotspots, monitoring, and network security. From these problems, the author recommends developing by implementing a proxy in building network infrastructure at the Rumbuk village office in the Sakra sub-district. The purpose of this research is to assist the village government in managing the network by monitoring, managing bandwidth, and improving the network security system using a proxy. So that the village government can improve services for the community in the field of information technology optimally. The development of network topology and hotspots is needed to make it easy for village governments to access networks, not only wired networks but also wireless networks. By implementing proxy in this network infrastructure to control all equipment and network users who are allowed to enter or not. Bandwidth settings for all network users are tailored to their individual needs. And the security system contained in the proxy is safe enough because the proxy can limit the access rights of every user who enters the network.DOI : 10.29408/jit.v3i2.2350